Extensive-Stage Small Cell Carcinoma Transformation From EGFR Del19-Mutant Lung Adenocarcinoma on Gefitinib at the Twelfth-Year Follow-Up Case Report - Kok, Victor C.; Lee, Chien-Kuan; Chiang, Yu-Hsin; Wang, Ming-Chih; Lu, Yen-Te; Cherng, Chiu-Chun; Lee, Pei-Yu; Wang, Ke-Bin (Frontiers in Oncology, 2021)
Introduction: The acquired resistance mechanisms in patients with epidermal growth factor receptor (EGFR)-mutant lung cancer, particularly adenocarcinoma (ADC), following treatment with an EGFR tyrosine kinase inhibitor (TKI) have received extensive investigations. The phenotypic transformation to small cell carcinoma (SCCT) has been estimated to occur in approximately 3% to 10% of patients treated with an EGFR-TKI. The prognosis after SCCT is extremely poor. Case Study: We report about SCCT that occurred 45 months after the initial diagnosis of ADC in an East Asian never-smoker woman with advanced-stage EGFR Del-19-mutant lung ADC treated with combined chemoradiotherapy before the era of insurance coverage for EGFR-TKIs in this country and subsequently gefitinib; deletion at codon 746-750 in exon 19 of the EGFR gene was ascertained in the original formalin-fixed paraffin-embedded lung biopsy tissue. Spinal cord compression at thoracic-12 level from SCCT was successfully relieved with neurosurgical treatment, chemotherapy with etoposide and cisplatin, and radiotherapy, while gefitinib treatment was maintained. Eleven months later, SCCT relapsed in the lung parenchyma, which was resected and was found to be sensitive to second-line weekly topotecan. Prophylactic cranial irradiation was subsequently administered. SCCT was confirmed by MALDI-TOF MS analysis of formalin-fixed paraffin-embedded tissues demonstrating the same exon 19 deletion. At the 12th-year follow-up, the patient remains relapse free with very good performance status. The novelty of this case is the successful interdisciplinary team effort to correct the spinal cord compression by maintaining the patient in an ambulatory state, non-stop use of gefitinib justified by the presence of activating EGFR mutation in SCCT tumor cells, and aggressive dose-intensive chemotherapy and radiotherapy for the SCCT that leads to an unprecedented prolonged remission and survival. This case also supports the observation that SCCT is chemotherapy sensitive, and thus, re-biopsy or complete tumor excision is recommended to understand the mutation profiles of the current tumor. Aggressive prudent administration of systemic chemotherapy obtaining optimal dose intensity leads to the successful management of the patient.